Catálogo de Camu Camu del Banco de Germoplasma del INIA - Imán Correa, Sixto Alfredo; Chuquizuta del Castillo, Badys; Samanamud Curto, Angelo Francisco; Ochoa Vásquez, Marjorie (Instituto Nacional de Innovación Agraria, 2022)
76 páginas